2017
DOI: 10.28945/3694
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Framework to Understand the Intrinsic Motivation Factors on University Students’ Behavioral Intention to Use a Mobile Application for Learning

Abstract: Aim/Purpose: By integrating a motivational perspective into the Technology Acceptance Model, the goal of this study is to empirically test the causal relationship of intrinsic motivational factors on students’ behavioral intention to use (BIU) a mobile application for learning. Background: Although the Technology Acceptance Model is a significant model, it largely remains incomplete as it does not take into consideration the motivation factors and/or outside influences in the adoption of new technology. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 61 publications
0
18
0
1
Order By: Relevance
“…According to previous studies, the actual use of an innovative information technology (IT) is approximately 40% attributed to behavioural intention to use the IT (Venkatesh & Bala, 2008). Behavioural intention is defined as a person's perceived likelihood that he or she will be engaged in a particular behaviour (Shroff & Keyes, 2017). Self-efficacy is identified as one of the important antecedents for the behavioural intention to use an innovative IT such as smartphones (Y.…”
Section: Interaction Competency Smartphone Selfefficacy and Behavmentioning
confidence: 99%
“…According to previous studies, the actual use of an innovative information technology (IT) is approximately 40% attributed to behavioural intention to use the IT (Venkatesh & Bala, 2008). Behavioural intention is defined as a person's perceived likelihood that he or she will be engaged in a particular behaviour (Shroff & Keyes, 2017). Self-efficacy is identified as one of the important antecedents for the behavioural intention to use an innovative IT such as smartphones (Y.…”
Section: Interaction Competency Smartphone Selfefficacy and Behavmentioning
confidence: 99%
“…In conclusion, the findings highlight the potential of tasks that involve gaming to contribute to the enhancement of intrinsic motivation, engagement and team building, which are so essential in educational context, as well as, future professional development as psychologist. As an example, It is well established that intrinsic motivation exerts a key and crucial influence on a wide arrange of learning outcomes, as achievement, satisfaction, and performance expectations [20] [15]. More research is needed to fully examine games based learning effects and determine how to achieve the best sustained intrinsic motivation, engagement and team building.…”
Section: Discussionmentioning
confidence: 99%
“…Game-based learning is an interactive learning methodology and instructional design strategy that integrates educational content and gaming elements, by delivering interactive, game-like formats of instruction to learners [55]. Moreover, game-based learning integrates aspects of experiential learning and intrinsic motivation with game applications that have explicit learning goals, thereby allowing learners to engage in complex, problem-solving tasks and activities that mirror real-world, authentic situations [56,57]. For example, results from a study conducted by Snow et al, [58] demonstrated that a computer game simulation of Newton's laws of motion was actively effective in helping non-physics students understand key concepts of force.…”
Section: Game-based Learning In Mathematics In Tertiary Education In mentioning
confidence: 99%